Open Source System for Smart Home Devices Based on Smartphone Virtual Assistant - Dwi Susanto; Faaris Mujaahid; Ramadoni Syahputra; Karisma Trinanda Putra (Journal of Electrical Technology UMY, 2019)
No doubt, the functionality of smartphones and the internet is now very diverse. Various features and applications in it are present to simplify human life, including the voice assistant feature. This study raises the theme of utilizing voice assistant for the purposes of controlling smart household devices based on the IoT module. The IoT NodeMCU module has an integrated WiFi chip, works with low power settings and supports flexible programming languages using the Arduino IDE. Testing using Android OS 5.0.2 version and 7.1.2 version generate four different results, which are 100% 83.33% accuracy for male voices and 83.33% 58.33% when tested using female voices. The accuracy is determined by several reasons i.e. system version, the quality of the microphone, noise, and voice articulation when giving commands to the Google Assistant.